2015
DOI: 10.1371/journal.pone.0134087
|View full text |Cite
|
Sign up to set email alerts
|

PGC−1α Promoter Methylation in Parkinson’s Disease

Abstract: The etiopathogenesis of sporadic Parkinson’s disease (PD) remains elusive although mitochondrial dysfunction has long been implicated. Recent evidence revealed reduced expression of peroxisome proliferator-activated receptor gamma coactivator−1 α (PGC−1α) and downstream regulated nuclear encoded respiratory complex genes in affected brain tissue from PD patients. We sought to determine whether epigenetic modification of the PGC−1α gene could account for diminished expression. In substantia nigra from PD patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
81
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(85 citation statements)
references
References 61 publications
3
81
0
1
Order By: Relevance
“…Similar observations have recently been reported in adult conditional parkin knock-out mice and mice overexpressing PARIS due to the reduction of PGC-1α levels (Stevens et al, 2015). Together, these studies indicate that the maintenance of PGC-1α levels in PD could offer neuroprotective therapeutic opportunities in PD (Zheng et al, 2010; Clark et al, 2011; Shin et al, 2011; Eschbach et al, 2015; Su et al, 2015). …”
Section: Discussionmentioning
confidence: 97%
“…Similar observations have recently been reported in adult conditional parkin knock-out mice and mice overexpressing PARIS due to the reduction of PGC-1α levels (Stevens et al, 2015). Together, these studies indicate that the maintenance of PGC-1α levels in PD could offer neuroprotective therapeutic opportunities in PD (Zheng et al, 2010; Clark et al, 2011; Shin et al, 2011; Eschbach et al, 2015; Su et al, 2015). …”
Section: Discussionmentioning
confidence: 97%
“…In conclusion, since the PARIS/PGC-1α cell death pathway appears to play a role in sporadic PD (Clark et al, 2011; Eschbach et al, 2015; Shin et al, 2011; Su et al, 2015; Zheng et al, 2010), therapeutic strategies aimed at inhibiting PARIS or maintaining PGC-1α function could be beneficial in both sporadic PD and PD due to mutations in parkin or PINK1 .…”
Section: Discussionmentioning
confidence: 99%
“…Recently, a new framework was proposed, linking free fatty acids and methylation status of the PGC‐1 α gene as an epigenetic contributor of sporadic PD: significant promoter‐proximal non‐canonical cytosine methylation of the PGC‐1 α gene was found in affected brain tissue from PD patients and it was shown that PGC‐1 α methylation was stimulated by the pro‐inflammatory fatty acid palmitate (Su et al . ).…”
Section: Park 2mentioning
confidence: 97%